Consolidation of Cargos in the Road Transport as a Key Method to Success - Zbigniew Łukasik; Aldona Kuśmińska-Fijałkowska; Jacek Kozyra; Sylwia Olszańska (Communications - Scientific letters of the University of Zilina, 2021)
The problem of consolidation of goods for the provider of logistic services, which is a third part that delivers goods from many suppliers to one business client in time horizon was analysed in this article. Every parcel has a fixed date of reception in the source and delivery schedule in a destination. In the age of highly developed economy, time pressure and costs, outsourcing is a condition necessary to improve the functioning of enterprises. New logistic chains, networks of terminals and intermodal connections are built every year to reduce the transport costs and improve the whole process. In this article, the authors presented the benefits resulting from consolidation of cargos in the road transport. Special emphasis was put on determination of the role of the transport costs reduction using the cargo consolidation services.